1999
DOI: 10.1530/eje.0.1410387
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists both stimulate and inhibit prolactin release in GH4ZR7 cells

Abstract: Prolactin secretion from the anterior pituitary gland is regulated by multiple factors including prolactin-release inhibiting factors (PIFs) and prolactin releasing factors. PIFs, however, usually dominate to exert a tonic inhibition in the biological system, and the physiological PIF is believed to be dopamine. However, there is accumulating evidence that dopamine can not only inhibit but also stimulate prolactin release. Many investigators believe that this is achieved by activating inhibitory and stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Seminal vesicles and vas deferens, including testis and epididymides, are also rich sources of adrenaline and noradrenaline in human semen (32). These catecholamines have been shown to enhance sperm motility, transport, capacitation, and acrosome reaction (33), and they are also involved in contraction of the seminal vesicles and inhibition of lipid peroxidation in spermatozoa (34).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal vesicles and vas deferens, including testis and epididymides, are also rich sources of adrenaline and noradrenaline in human semen (32). These catecholamines have been shown to enhance sperm motility, transport, capacitation, and acrosome reaction (33), and they are also involved in contraction of the seminal vesicles and inhibition of lipid peroxidation in spermatozoa (34).…”
Section: Discussionmentioning
confidence: 99%
“…Given that cabergoline half-life in cows is 19 h (EMA, 2015), and due to its high affinity for dopamine D 2 -like receptors (Kvernmo et al, 2006), the occurrence of the PRL rebound on d 14 after injection may be related to a midterm feedback of pituitary's lactotrophs, decreasing the release of natural dopamine, which will result in a rise of PRL. Mechanism of PRL rebound in rats after dopamine withdrawal was explained by Chen et al (1993) and Chang and Shin (1999), who demonstrated that dopamine acts on D 2 receptors both to inhibit and to stimulate PRL release. We hypothesize that this may be related to the decrease of the activity of tyrosine hydroxylase (TH), the rate-limiting key enzyme in the biosynthesis and availability of catecholamines (i.e., dopamine, noradrenaline, and adrenaline) during the cabergoline treatment.…”
Section: Prolactin In Plasmamentioning
confidence: 99%
“…Although this effect has been observed in several laboratories, there is contradictory evidence regarding the pathways involved in the stimulation of secretion. Some laboratories have shown that a D2 receptor subtype is involved (Burris et al, 1991;Chang & Shin, 1999), while others have proposed that D5 receptors may play a role in the stimulatory response (Porter et al, 1994). Similarly, a pertussis toxin sensitive G-protein pathway was suspected in one study (Tagawa et al, 1992) but had no effect in other studies (Burris et al, 1992;Chang et al, 1997).…”
Section: Assumptions and Experimental Testsmentioning
confidence: 99%